Isyarat-Isyarat Pendidikan dalam Al-Quran - Julhadi Julhadi (2022)
Education is an activity program that contains an educational component that can improve human resources for the better. Education is a very important capital in living social life. There are several educational cues contained in the Qur'an, including educational goals, educational subjects, educational objects, teaching and learning obligations, educational methods and educational evaluations. All of these cues can affect the success of education carried out by educators.